Companion to sexuality studies - Naples, Nancy A. (Wiley Blackwell, 2020)
An inclusive and accessible resource on the interdisciplinary study of gender and sexuality Companion to Sexuality Studies explores the significant theories, concepts, themes, events, and debates of the interdisciplinary study of sexuality in a broad range of cultural, social, and political contexts. Bringing together essays by an international team of experts from diverse academic backgrounds, this comprehensive volume provides original insights and fresh perspectives on the history and institutional regulatory processes that socially construct sex and sexuality and examines the movements for social justice that advance sexual citizenship and reproductive rights. Detailed yet accessible chapters explore the intersection of sexuality studies and fields such as science, health, psychology, economics, environmental studies, and social movements over different periods of time and in different social and national contexts. Divided into five parts, the Companion first discusses the theoretical and methodological diversity of sexuality studies.Subsequent chapters address the fields of health, science and psychology, religion, education and the economy. They also include attention to sexuality as constructed in popular culture, as well as global activism, sexual citizenship, policy, and law. An essential overview and an important addition to scholarship in the field, this book: Draws on international, postcolonial, intersectional, and interdisciplinary insights from scholars working on sexuality studies around the world Provides a comprehensive overview of the field of sexuality studies Offers a diverse range of topics, themes, and perspectives from leading authorities Focuses on the study of sexuality from the late nineteenth century to the present Includes an overview of the history and academic institutionalization of sexuality studies The Companion to Sexuality Studies is an indispensable resource for scholars, researchers, instructors, and students in gender, sexuality, and feminist studies, interdisciplinary programs in cultural studies, international studies, and human rights, as well as disciplines such as anthropology, psychology, history, education, human geography, political science, and sociology.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; premier cycle; psychologie; queer; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; thématiques; études de genres; études des sexualités

« A fairly typical boy », « a fairly typical girl » - Piccand, Laura (Emulations - Revue de sciences sociales, 2018)
Les stades dits de Tanner sont une série de photographies permettant d’évaluer le développement pubertaire des filles et des garçons. Utilisés dans la clinique et la recherche médicales contemporaines, leur histoire remonte aux années 1950. Cet article propose de revenir sur le contexte de production de cet artefact et d’interroger la façon dont il est partie prenante de la construction socio-historique de la binarité du sexe dit biologique. La puberté comme objet scientifique et médical est en effet un lieu crucial de production, de reproduction et de reconfiguration du genre.
Number: 15
Keywords: 1900-1999; 1950-1959; 1960-1969; angleterre; approches et analyses; cours; discipline; discours dominant; europe; inégalités; londres; patriarcat; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2051; sociologie; sofia; systèmes d'oppressions; thématiques

Les sujets intersexes peuvent-ils (se) penser ? - Charlebois, Janik Bastien (Socio, 2017)
Les personnes intersexuées sont rendues invisibles par les mythes sociaux sur l’hermaphrodisme et le troisième sexe. Pourtant, certaines d’entre elles se politisent afin de faire cesser les interventions non consensuelles que la médecine pratique sur elles dans le but de conformer leur corps aux normes « mâle » et « femelle ». Saisis de cette critique, les médecins s’investissant dans la prise en charge intersexe l’invalident partant du postulat que ces personnes qui prennent la parole dans l’espace public sont rares. Pour comprendre cette faible présence des perspectives intersexes critiques, nous mobilisons les concepts de subjectivation politique de Lamoureux (2001) et de Gaulejac (2007), de même que celui d’injustice épistémique de Fricker (2007). À partir de données empiriques et de savoirs construits sur le terrain par l’auteure à titre de chercheure engagée intersexe, cet article relève les mécanismes institutionnels encadrant les possibilités de construction d’une position de sujet réflexif, puis les composantes requises au développement d’une position d’acteur sujet.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; intersexuation; personnes intersexes; premier cycle; périodes historiques; queer; québec; régions géographiques; santé; sciences humaines; sexualité; soc2014; soc3113; sociologie; systèmes d'oppressions; thématiques

A messy trajectory: From medical sociology to crip theory - Egner J. (Research in Social Science and Disability ; 9, 2016)
Purpose The purpose of this paper is to draw attention to the work of sociologists who laid the foundation for queer and crip approaches to disability and to address how queer and crip theory has and can help to re-conceptualize our understandings of health, illness, disability, and sexuality. Methodology/approach This paper is an examination of historical moments and prominent literature within medical sociology and sociology of disability. Sociological and popular understandings of disability and sexuality have often mirrored each other historically. Although this literature review focuses primarily on medical sociology and disability studies literature, some works of scholars specializing in gender studies, sexuality, literature, history, and queer studies are also included Findings In this paper, I argue that the medicalization and pathologization of human differences specifically as it pertains to sexuality and disability within the medical sociological literature have led to constructionist, social model, and feminist critiques. It is these critiques that then laid the foundation for the development of queer and crip theoretical approaches to both disability and sexuality. Originality/value Crip and queer approaches to disability provide a clear call for future sociological research. Few social science scholars have applied queer and crip approaches in empirical studies on disability. The majority of work in this area is located in the humanities and concerned with literary criticism. A broader array of empirical work on the intersection of sexuality and disability from queer/crip perspectives is needed both to refine these postmodern theoretical models and to examine their implications for the complex lived experience that lies at the intersection of sexuality and disability. In queering disability and cripping sexuality and gender, we may be able not only to more fully conceptualize disability, sexuality, and gender as individual social categories, but also to more fully understand the complex intersection of these social locations.
Keywords: EDI; approches et analyses; care; cours; crip; discipline; histoire et politique; premier cycle; queer; ressource en ligne; santé; sciences humaines; sex1920; sociologie; sofia; thématiques

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Transidentités: ordre & panique de genre : le réel et ses interprétations - Espineira, Karine; Bertini, Marie-Joseph (L'Harmattan, 2015)
Engagée dans une recherche sur le terrain transidentitaire, la chercheuse s'attache à croiser état des lieux du terrain associatif et militant trans avec l'histoire des définitions de la médecine légale, mettant à jour la politisation des groupes, les apports des nouveaux médias et les effets de la médiatisation sur les personnes transgenres. Cet ouvrage est complémentaire du titre Médiacultures: la transidentité en télévision, édité simultanément.
Section: 263 pages ; 24 cm.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; histoire et politique; militance; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; thématiques; transféminisme

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

Hormones et reconfiguration des identités sexuelles au Brésil - Sanabria, Emilia (Clio. Femmes, Genre, Histoire, 2013)
Les hormones sexuelles sont des objets hybrides et complexes à la frontière du sexe et du genre. Dès lors qu’elles sont synthétisées sous forme pharmaceutique, elles peuvent attribuer des caractéristiques sexuelles au corps de manière partiellement exogène à celui-ci. Il s’en suit que l’utilisation clinique qui en est faite est socialement réglementée. À travers une analyse de divers contextes d’utilisation des hormones observés à Bahia, au Brésil, cet article montre que le dualisme sexuel est le produit de pratiques de régulation biomédicales qui visent à encadrer la circulation des hormones. Le sens du terme local « hormônio » n’est pas pleinement recoupé par celui d’hormone, qu’il excède. L’emploi commun qui est fait au Brésil du singulier procure au terme « hormônio » une qualité fluide et homogène. Dans ce contexte, les hormones sont comprises comme une sorte de substance qui peut circuler entre les corps. Cette conceptualisation des hormones comme une substance a des implications pour le statut ontologique des corps et révèle la relative plasticité de la relation sexe/genre.
ISBN: 9782701177816 Number: 37 Publisher: Éditions Belin
Keywords: 1900-1999; 1950-1959; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du sud; amériques; approches et analyses; brésil; corps; cours; discipline; discours dominant; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

La régulation sociale des minorités sexuelles: l'inquiétude dela différence - Corriveau, Patrice; Daoust, Valérie; ProQuest (Firme) (Les Presses de l'Université du Québec, 2011)
Successivement condamnées par la religion, criminalisées par le droit pénal et finalement médicalisées, les minorités sexuelles ont subi une forte répression institutionnelle. Depuis, les luttes des mouvements gais et lesbiens ont conduit, dans certains pays, à la reconnaissance des droits des homosexuels au mariage et à la parentalité. Toutefois, l’homosexualité est encore trop souvent perçue comme une menace à la tradition et à l’ordre « naturel ». Réunissant les contributions de chercheurs en sociologie, en philosophie, en criminologie, en histoire, en anthropologie, en sexologie et en travail social, cet ouvrage porte sur les multiples modes de régulation institutionnelle et sociale des minorités sexuelles. Tout en exposant les différentes pratiques de répression employées par le passé, les auteurs traitent de sujets contemporains comme l’homophobie dans les écoles et l’homoparentalité. Soulevant des questions de justice sociale, ils rappellent que tous, gais et lesbiennes y compris, sont engagés dans le processus de régulation des minorités sexuelles.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; belgique; canada; cours; criminologie; discipline; europe; histoire; homophobie; hétérosexisme; justice sociale; militance; philosophie; premier cycle; queer; québec; régions géographiques; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; travail social; études gaies et lesbiennes

Le bouclier thérapeutique: discours et limites d’un appareil de légitimation - Espineira, Karine (Le sujet dans la cité, 2011)
En 1982, le professeur René Küss plaide à la télévision pour un protocole appelant à distinguer entre « vrais » et « faux » trans’ : de « vrais trans’ » ne causent aucun trouble dans le genre : on leur accorde une aide exceptionnelle (l’opération) par laquelle - hommes devenus femmes ou femmes devenues hommes - ils rentrent dans l’ordre du genre et de l’identité. Telle est l’une des premières expressions de ce que nous proposons d’appeler le « bouclier thérapeutique ». Les trois décennies qui suivent voient s’affronter les affirmations transidentaires et l’idéologie dominante des « traitants ». Appareil de légitimation d’un ordre ancien, le « bouclier thérapeutique » ne serait-il plus aujourd’hui pour ses partisans que le dernier vestige d’une ère marquée par l’effritement d’un deuxième bouclier, juridique celui-ci, garantissant que la libre disposition de l’état civil reste une exception ? Sur ces questions qui interrogent profondément les représentations que nos sociétés se font d’elles-mêmes, peut-être le temps est-il venu d’ouvrir la route tracée par la recherche en sciences sociales et humaines aux nouveaux paradigmes amorcés par les Études de Genre.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; care; cours; discipline; discours; europe; france; inégalités; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; système médical; systèmes d'oppressions; thématiques; transféminisme; violences; violences institutionnelles; violences médicales

Transidentité: de la théorie à la politique. Une métamorphose culturelle entre pragmatisme et transcendance - Espineira, Karine (L'information psychiatrique, 2011)
Du décret français du 10 février 2010 aux travaux de réécriture lancés par le DSM et la CIM, les questions transidentitaires doivent être discutées, appréhendées sur le plan théorique aussi bien que politique. Le schisme entre les associations d’usagers, les trans’ en demande et/ou en obligation de suivi, et les équipes hospitalières spécialisées dans la prise en charge de ce public, pour le cas de la France tout particulièrement, a une histoire intimement liée à un ordre présumé du social et de ses acteurs en termes de genre dans une vision binaire de la société. La demande de reconnaissance de savoirs, d’expertises du terrain transidentitaire s’est heurtée, dès le début des années 1980, au bouclier thérapeutique , que l’on peut définir comme l’argument ultime de l’instance médico-légale en charge du sujet transsexe, écartant les autres sujets/trajets trans’, pour mettre à distance toute intervention du politique, des sciences humaines et sociales dans ce qui est devenu un paradigme théorique : le changement de sexe est d’abord un changement culturel de genre. Enfin, l’instance médico-légale s’efforce d’ignorer sa propre politisation et militance. Partagé entre la volonté de résister et de participer face/avec un protocole inadapté, inefficace et culturellement obsolète, le terrain a connu ses propres mouvements s’interrogeant, s’interpellant sur l’esprit de la méthode. La question trans’ compte désormais autant de politiques que de groupes. La théorisation du fait trans’, trouve sa légitimité non pour revenir seulement sur l’inégalité homme/femme, mais pour lutter du même élan contre toute forme d’inégalité et de stigmatisation. Le terrain transidentitaire s’est profondément transformé, les outils pour l’appréhender comme le paradigme théorique lui-même, se doivent une chose : évoluer.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; militance; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; sociologie; thématiques; transféminisme; violences; violences médicales

The Intersex Enchiridion: Naming and Knowledge - Holmes, Morgan (Somatechnics, 2011)
The 2006 Lawson Wilkins Pediatric Endocrinology Society (LWPES) consensus to alter clinical language from ‘intersex’ to Disorders of Sex Development (DSD) has not met its stated objective of destigmatizing the ‘intersex’ label. Rather, DSD works to paper over a problematic understanding of morphological variation as disease. This article interrogates the development of DSD terminology in the clinical context of treating intersex and argues that ‘DSD’ reinstitutionalises clinical power to delineate and silence those marked by the diagnosis; that this silencing is precisely the point of the new terminology; and that it is against that retrenchant impulse that we must protect the viability of ‘intersex’ by continuing its critical deployment. This paper is based on an application of embodiment studies models of critique, combined with an orientation grounded in queer theory to critically interrogate the development of both DSD language and of the ‘new’ guidelines for clinical use, and of the Handbook for Parents that were developed out of the 2006 LWPES meetings. Some of my critique is based on work done over an 18-year period with adults who created the contemporary intersex movement, and on my previous research (in particular: Holmes 2002, 2008, 2010). The point of the argument is not to determine which diagnostic language is superior, but to retain the hard-won right to secure for ourselves the ability to operate socially without the stamp of ‘disorder’ or ‘disease’ strictly delineating what counts as ‘truth’ with regard to embodiment. In this sense, the argument applies to and is drawn out of a larger disability scholarship and activism framework that refuses to permit medicine the final voice in defining our bodies and our selves. The title refers to an older handbook, the enchiridion as a gesture toward the need to retain fundamental knowledge of self that intersexed persons can trace back to a more flexible understanding of embodied differences than the language of disorder asserts in the new Handbook for Parents.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; identité; intersexuation; militance; personnes intersexes; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; thématiques; violences; violences médicales; états-unis

Sport et bicatégorisation par sexe : test de féminité et ambiguïtés du discours médical - Bohuon, Anaïs (Nouvelles Questions Féministes, 2008)
Dès les années 30, des sportives font l’objet d’un procès de virilisation dans des épreuves d’athlétisme en raison de morphologies jugées trop « masculines ». Ces athlètes se rapprochent des hommes non seulement par le physique, mais aussi par leurs performances. Des soupçons sont alors émis quant au sexe des sportives. En 1966, un test de féminité est instauré par le monde médical sportif afin de contrôler le sexe des concurrentes et s’assurer que celles-ci ne bénéficient pas d’avantages physiques que les femmes ne sont pas censées posséder. Notre article consiste à montrer les ambiguïtés des discours médicaux face aux controverses soulevées par le test de féminité qui, dévoilant les niveaux pluridimensionnels de l’identité sexuée, obligent le milieu médico-sportif à s’interroger sur la définition d’une « vraie femme ».
Number: 1
Keywords: 1900-1999; 1930-1939; 1960-1969; approches et analyses; cours; discipline; discours dominant; europe; france; postmodernisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2051; sociologie; sport; systèmes d'oppressions; thématiques

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Intersexe et transsexualités : Les technologies de la médecine et la séparation du sexe biologique du sexe social - Löwy, Ilana (Cahiers du Genre, 2003)
Le sexe social est construit sur un mode binaire. Par contre, le sexe biologique se présente comme un continuum, avec, aux deux extrêmes, les « sexes biologiques » clairement définis et, au milieu, une large gamme de situations intermédiaires — des individus « intersexe ». De tels individus remettent en cause nos certitudes sur la stabilité des catégories « homme » et « femme ». Cet article trace l’histoire des interventions médicales ayant pour but de corriger l’anomalie de l’intersexe et de produire des êtres humains dont le corps ne remet pas en cause la bipolarité du féminin et du masculin. Il suit les débats sur les liens supposés entre intersexualité et homosexualité puis expose la transition du traitement de l’intersexualité à celui de la transsexualité. Il étudie enfin le rôle des nouvelles techniques de la médecine dans la séparation entre le « sexe » et le « genre ». La possibilité de moduler les paramètres du « sexe biologique » permet alors une réflexion sur le « sexe social » comme variable indépendante des structures biologiques.
Number: 1 Publisher: L'Harmattan
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Section: xviii, 278 p
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires